Fear of missing out? Personality and plasticity in food neophilia by wild vervet monkeys, Chlorocebus pygerythrus. (September 2022) - Nord, Christina; Bonnell, Tyler; Roth, Delaney; Clarke, Madison; Dostie, Marcus; Henzi, Peter; Barrett, Louise
Abstract : Animals often differ in their responses towards novelty, and sometimes these differences are consistent across individuals. Here, we explored interindividual variation in neophilia towards novel foods by recording whether animals ingested novel food stuffs ( N individuals  = 116; N trials  = 276) in three troops of wild vervet monkeys. We tested for the effects of individual level variables, between-individual variation (i.e. personality), within-individual variation (i.e. plasticity) and variation in testing conditions (e.g. ecological conditions, proximate social environment). We found that our animals showed consistent differences towards eating novel foods, with lower-ranking animals displaying a more neophilic response than higher-ranking animals, and that neophilia was socially facilitated. Social facilitation did not depend on whether the partner was foraging, the social association between the focal and their partner or relatedness, indicating that the mere presence of another increased the likelihood that animals would eat the novel food. We also found some evidence that animals responded differentially to variation in their proximate social environment, as some, but not all, animals were more likely to eat the novel food as the number of partners increased, whereas others were not. Our results underscore the importance of testing behaviour and cognition under natural conditions rather than always doing so under strictly controlled settings and controlling for possible confounding factors statistically rather than controlling the testing conditions themselves. Highlights: Vervet monkeys showed personality in food neophilia. Lower-ranking animals were more neophilic than higher-ranking animals. Neophilia was socially facilitated. Social facilitation was not dependent on social association or relatedness. Neophilia was plastic under different social contexts.